2004
DOI: 10.1105/tpc.020743
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Plant U12-Dependent Intron Splicing Efficiency

Abstract: Factors affecting splicing of plant U12-dependent introns have been examined by extensive mutational analyses in an in vivo tobacco (Nicotiana tabacum) protoplast system using introns from three different Arabidopsis thaliana genes: CBP20, GSH2, and LD. The results provide evidence that splicing efficiency of plant U12 introns depends on a combination of factors, including UA content, exon bridging interactions between the U12 intron and flanking U2-dependent introns, and exon splicing enhancer sequences (ESEs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 70 publications
4
54
0
Order By: Relevance
“…Incidentally, our study showed that NGS data can be exploited for further exploration of the expression strategy of geminiviruses. The splicing signals found at the border of the MMDaV intron are identical to those conserved in the characteristic U2 plant introns (Lewandowska et al, 2004), but they differ slightly from those reported in all the other geminiviruses known to bear an intron in the complementary-sense transcript (Fig. S3).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Incidentally, our study showed that NGS data can be exploited for further exploration of the expression strategy of geminiviruses. The splicing signals found at the border of the MMDaV intron are identical to those conserved in the characteristic U2 plant introns (Lewandowska et al, 2004), but they differ slightly from those reported in all the other geminiviruses known to bear an intron in the complementary-sense transcript (Fig. S3).…”
Section: Discussionmentioning
confidence: 60%
“…4a). This intron contains the consensus 59 and 39 splice sites and branchpoints characteristic of the U2 plant introns (Lewandowska et al, 2004) and has an RNA U+A content (59.4%) close to the minimum needed for its efficient splicing (Goodall & Filipowicz, 1989;Simpson & Brown, 1993). Interestingly, an intron with similar features can also be predicted in a similar position of the complementary-sense strand of the CCDaV genome.…”
Section: Y Ma and Others 2426mentioning
confidence: 90%
“…The intron sequences together with the fragments (>55 bp) from the original 5′- and 3′-exons were isolated from Arabidopsis genomic DNA by PCR and introduced to the plant expression vector pDH515 within an intronless zein gene using the unique Bam HI restriction site [42,43]. For the mutant intron construct generation (with different tRNA types), a two-step PCR-based approach was used.…”
Section: Methodsmentioning
confidence: 99%
“…The common U2-type splices GT-AG introns, socalled because they have GT and AG dinucleotides at the 5 0 and 3 0 end, respectively. The second is known as the U12 type, and it splices the very rare -and misleadingly named -AT-AC introns, which have a range of dinucleotides at their ends (confusingly, most often GT-AG) (Lewandowska et al, 2004); however, the two types are sufficiently similar for us to treat them as a single entity in this review. Eukaryotes vary considerably in the length and abundance of their introns (Deutsch and Long, 1999), yet most seem to have them and even unicellular eukaryotes have extremely complex spliceosomes for their removal (Jurica and Moore, 2003;Nilsen, 2003).…”
Section: Introductionmentioning
confidence: 99%